Antropologiczno-egzystencjalne podstawy Josepha Maréchala studiów nad mistyką - Bańka, Aleksander (Folia Philosophica, 2018)
The paper aims at revealing theoretical basis of studies in mysticism conducted by Belgian Jesuit Joseph Maréchal. It is focused on the key issue of unification of man and God. This problem has its precisely defined, anthropological and existential context which in Maréchal’s work comes down to the question on the nature of the substantial centre of the soul in which this unification shall take place. The paper argues that in Maréchal’s analysis the centre of the soul, or substantial ego, equates with the possible intellect and in some cases it might be taken as not only the ontic basis for acts of cognition, but also for mystical phenomena.